Obiekty, urządzenia techniczne regionu Podhala w edukacji dzieci - Dworska-Kaczmarczyk, Urszula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Poznanie przez dziecko dziedzictwa kulturowego swojej małej ojczyzny stanowi podstawę do rozbudzania tożsamości regionalnej. W niniejszym artykule poruszono problematykę dziedzictwa techniki. Omówione będą najważniejsze obiekty techniki regionu Podhala, które można wykorzystać w edukacji dzieci.

The knowledge of the cultural heritage of small homeland among children is the basis for the creation of regional identity. This article will be discussed the issues of the heritage of technics. The most important technical objects of the Podhale region will be discussed, which can be used in children's education.
Technical Devices, Technical Objects of the Podhale Region in the Education of Children
Keywords: obiekty techniki; dziedzictwo techniki; region Podhala; technical objects; heritage of technics; Podhale region